THE IMPLEMENTATION OF MADRASAH PRINCIPAL IN DEVELOPING INCLUSIVE EDUCATION FOR STUDENTS WITH SPECIAL NEEDS AT MTS BONTOCINDE GOWA - Yani, Sri Andri; Syamsudduha, St.; Ismail, Wahyuni; Ikbal, Muhammad (Idaarah: Jurnal Manajemen Pendidikan, 2024)
This research examines how the leadership of the madrasah principal at MTs Inclusion Bontocinde Gowa develops inclusive education for students with special needs. It explores three key questions: the nature of the principal’s leadership, how inclusive education is implemented, and how this leadership supports inclusive education. Using a qualitative phenomenological approach, data were collected through observations, documentation, and interviews. The study finds that while inclusive education is effectively implemented, challenges remain in funding, teacher quality, and infrastructure. The principal’s leadership is crucial, though teacher roles and parental involvement need improvement. The study suggests enhanced government support and ongoing development of inclusive practices.